The biographical encyclopedia of Islamic philosophy - Leaman, Oliver, 1950- (Bloomsbury Academic, 2015)
Philosophy flourished in the Islamic world for many centuries, and continues to be a significant feature of cultural life today. Now available in paperback, The Biographical Encyclopedia of Islamic Philosophy covers all the major and many minor philosophers, theologians, and mystics who contributed to its development. With entries on over 300 thinkers and key concepts in Islamic philosophy, this updated landmark work also includes a timeline, glossary and detailed bibliography. It goes beyond philosophy to reference all kinds of theoretical inquiry which were often linked with philoso.